Phonocardiography and Photoplethysmography Circuit for Integrated Physiological Signal Acquisition - Giri, Adesh; Chaskar, Uttam (2023 World Conference on Communication & Computing (WCONF), 2023)
Phonocardiography and photoplethysmography are two crucial non-invasive techniques for studying the physiological parameters of cardiovascular diagnosis. The PCG signal records heart sounds and reveals information about cardiac functioning by analysing the recorded sounds. PPG is an optical technique that measures relative changes in the blood volume of living tissue. This research paper presents the design, development, and testing of the circuit that can capture heart sounds as well as record changes in blood volume at the fingertip. This circuit facilitates compatibility with the digital storage oscilloscope and the Arduino. The aim of the research is to provide an affordable and versatile circuit that has the capabilities to measure accurate and simultaneous acquisition of PCG and PPG signals from the same subject with the flexibility of digital platforms for signal processing and analysis. The results demonstrate the circuit's effectiveness in acquiring better-quality PCG and PPG signals with minimal interference.